Memahami Tugas Utama Hamba Tuhan Berdasarkan Surat II Timotius 4:1-5 Dan Aplikasinya Pada Masa Kini - Kejar Hidup Laia (Sekolah Tinggi Teologi Berita Hidup, 2020)
Abstract: The passages 2 Timothy 4: 1-5 describes the task of a servant of God. The intended form of duty and calling included the task and call to always preach the gospel, in all situation good or not. Reprimand and advise the wrong and provide healthy teaching. The task of preaching the gospel is the task of calling for service for all believers. This task must be carried out seriously and with patience. God's servant must have courage to reveal the truth to anyone, including the rulers. But before carrying out that task, the Servant of God must equipted himself first with the Word of God and always give a place to the Holy Spirit to dwell in him because by the Holy Spirit a person can able to control himself, suffer patiently and carry out his ministry to the end. Being a Servant of God has qualifications in 1 Tim. 3: 2 Paul says that as a servant of God it must be